1993
DOI: 10.1136/ard.52.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Altered Golgi apparatus in hydrostatically loaded articular cartilage chondrocytes.

Abstract: Objectives Articular cartilage proteo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 24 publications
4
26
0
1
Order By: Relevance
“…Our results agree with those of previous studies (34,35,46), demonstrating that chondrocytes, like other cells, respond to mechanical loads in monolayer culture. In monolayer culture, calvarial bone cells release prostaglandin E2 in response to cyclic biaxial mechanical strains (4) and neonatal rat cardiac myocytes increase c-fos gene expression, total RNA levels, and phosphoinositide turnover (23) in response to stretching.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Our results agree with those of previous studies (34,35,46), demonstrating that chondrocytes, like other cells, respond to mechanical loads in monolayer culture. In monolayer culture, calvarial bone cells release prostaglandin E2 in response to cyclic biaxial mechanical strains (4) and neonatal rat cardiac myocytes increase c-fos gene expression, total RNA levels, and phosphoinositide turnover (23) in response to stretching.…”
Section: Discussionsupporting
confidence: 96%
“…At 30 MPa, continuous but not cyclic hydrostatic pressure alters chondrocyte Golgi apparatus and decreases proteoglycan synthesis (35).…”
Section: Figmentioning
confidence: 99%
“…Earlier reports of the effects of HP have shown that continuous high HP leads to a reversible depolymerization of microtubules in vitro (50), a change from the normal stacked appearance of the Golgi apparatus to a tightly packed perinuclear clump (33), and an inhibition of total proteoglycan and protein synthesis in bovine chondrocytes (32,34). In line with our results, a 50-MPa HP treatment was recently shown to increase hsp70 mRNA levels in chondrocyte-like HCS-2͞8 cells (51).…”
Section: Discussionsupporting
confidence: 81%
“…High continuous hydrostatic pressure (HP) inhibits proteoglycan synthesis and secretion, reduces the steady-state level of aggrecan mRNA, alters the shape of the Golgi apparatus, and inhibits the stress fiber organization of microfilaments (32)(33)(34)(35). These findings prompted us to investigate whether such conditions would be adverse and induce stress response in the cells that synthesize cartilage-specific macromolecules.…”
mentioning
confidence: 99%
“…In addition, loading may affect the apparatus for transcription and translation differently. Studies (37) have shown that high pressure can cause changes in cell morphology and disorganization of the Golgi and microtubules in chondrocytes. Compression of cartilage explants also reduces cell volume and the volumes of several intracellular organelles; however, the volume of the Golgi remains unaffected by static compression of up to 50% strain (38).…”
Section: Discussionmentioning
confidence: 99%